FACEBOOK MESSENGER SEBAGAI MEDIA PROMOSI KESEHATAN REPRODUKSI REMAJA STUDI DI SMP MUHAMMADIYAH DEPOK SLEMAN YOGYAKARTA - Harpeni Siswatibudi; Ira Paramastri; Luthfan Lazuardi (Jurnal Permata Indonesia, 2016)
Abstract : Problems related to adolescent reproductive health, often stem from a lack of information, understanding and awareness to reach a state of healthy reproduction. Riset Kesehatan Dasar in 2013 than showed from the overall teen 10-24 years, the status are not married as much as 76.1%. In the group of adolescents with the status of unmarried males 3.0% and females 1.1% answered ever having sex. In addition there where the data of pregnancy at the age of less than 15 years at 2.6%. Given the development of social networking technologies and characteristics of young people, provision of adolescent reproductive health messages through facebook messenger can be used as a channel for the promotion of adolescent reproductive health. To determine the effectiveness of facebook messenger for promoting adolescent reproductive health. This quasi-experimental research, using the treatment group and the control group (nonequivalent control group design). The research sample were students of SMP Muhammadiyah I and SMP Muhammadiyah II Depok Depok many as 66 students. Instruments used in the form of a questionnaire. Analysis of the data was processed using different test averages and test different proportions. There were a difference in the improvement of knowledge between the control group and the treatment group indicated by p_value 0.000 (p < 0.05), but did not show any significant differences in the attitude (p > 0.05; p = 0.302) as well as the intention to avoid premarital sexual behavior (p > 0.05; p = 0.777). There were the effect of the message Adolescent Reproductive Health through facebook messenger to the increase in the mean score of knowledge, but there was no significant difference in mean values attitudes and intentions away from the teens in premarital sexual behavior.